Transthoracic ultrasonography in the assessment of interstitial lung disease in patients with systemic sclerosis - Shasanka Sekhar Das; Saubhik Kanjilal; Mridul Kanti Das; Avas Chandra Ray; Kausik Munsi; Parasar Ghosh (Asian Journal of Medical Sciences, 2023)
Background: Transthoracic ultrasonography was considered, sometimes in the past as unsuitable for the assessment of lung but it eventually emerged as an important tool in the diagnosis and in guiding treatment of various lung and pleural diseases. Several studies in the past proved it to be a useful complementary tool in the detection of interstitial pulmonary fibrosis. Aims and Objectives: This study aims to assess the utility of transthoracic uultrasonography (TUS) in comparison to high-resolution computed tomography (HRCT) thorax in the detection of interstitial lung disease (ILD) in systemic sclerosis (SSc) patients. Materials and Methods: SSc patients with HRCT proven ILD were identified and classified according to Warrick’s score. Sonographic evidence of ILD in these patients were judged by the presence of B-lines or ultrasonic lung comets (ULCs). Each procedure was studied and interpreted by two independent examiners blinded about the patient’s clinical and radiological features. Standard spirometric measurements were performed in all patients. Results: A highly significant positive linear correlation between ULCs and Warrick’s score was found in this study (r=0.83, P≤0.001). ULC score had moderate negative correlation with forced expiratory volume in 1 s (FEV1) % p (r=−0.60, P=0.001) and weak negative correlation with forced vital capacity (FVC) % p (r=−0.45, P=0.01) and FEV1/FVC % (r=−0.42, P=0.02). Conclusion: USG lung can be suggested as a useful non-invasive tool in the detection of ILDs in scleroderma patients.